Powieść Andrija Semiankiwa Tańce z kośćmi – ukraiński thriller medyczny - Zambrzycka, Marta (Studia Ukrainica Posnaniensia, 2024)
The topic of the article is the specificity of a medical thriller based on the novel Danc-ing with Bones (Танці з кістками) (2022) by Andriy Semyankiv. The study points out the specific features of a medical thriller and their reflection in Semyankiv’s literary work. This novel has its own specificity due to the local political and economic contexts of Ukraine. It fully reflects the features of the genre, while at the same time not being a literary cliché. The author also tries to analyse the peculiarities of the phenomena of fear and anxiety, which are the basis of the content of this medical thriller. In an original way, the writer indicates the connection between these feelings and biocontrol.